Safe overwintering method for macrobrachium nipponense parents - JIANG SUFEI; FU HONGTUO; XIONG YIWEI; WU YAN; GONG YONGSHENG (2010)
The invention discloses a safe overwintering method for macrobrachium nipponense parents, which mainly comprises selection of a parent overwintering temporary culture pond, overwintering pretreatment, construction of overwintering conditions, parents matching and density and overwintering feeding management technology and the like. The method is an overwintering method suitable for macrobrachium nipponense biology, ethology and ecology, the method can furthest improve the overwintering survival rate of the macrobrachium nipponense, and the overwintering survival rate can reach over 85 percent. The method reduces the overwintering loss of the macrobrachium nipponense, directly increases the economic benefit, provides reliable assurance for conservation and overwintering of good strains of the macrobrachium nipponense, and is helpful for improving the economic benefit of macrobrachium nipponense culture and promoting healthy and sustainable development of the macrobrachium nipponense breeding industry in China.